2022
DOI: 10.1007/s11162-022-09678-8
|View full text |Cite
|
Sign up to set email alerts
|

Thx 4 the msg: Assessing the Impact of Texting on Student Engagement and Persistence

Abstract: As colleges and universities strive to increase persistence and aid students in reaching graduation, they are utilizing alternative communication strategies like text messaging. Behavioral economics researchers suggest personalized, regular nudges can help college students make decisions that positively impact their college career and keep them on track for graduation. The current study presents the results of a randomized field experiment where a text messaging program was implemented in a large college at a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…Quantitative data on student engagement with the texting platform and opt-out rates were collected during the spring semester through the texting program’s platform. These data were linked to students’ administrative records and quantitative analyses revealed that students in the treatment group were significantly more likely to persist to the end of the semester than were their otherwise similar counterparts in the control group (Tippetts et al, 2020). A cost analysis was done in conjunction with the intervention that revealed text messaging to be a moderately cost-effective strategy for improving persistence in the college (Zick et al, 2020).…”
Section: Methodsmentioning
confidence: 99%
“…Quantitative data on student engagement with the texting platform and opt-out rates were collected during the spring semester through the texting program’s platform. These data were linked to students’ administrative records and quantitative analyses revealed that students in the treatment group were significantly more likely to persist to the end of the semester than were their otherwise similar counterparts in the control group (Tippetts et al, 2020). A cost analysis was done in conjunction with the intervention that revealed text messaging to be a moderately cost-effective strategy for improving persistence in the college (Zick et al, 2020).…”
Section: Methodsmentioning
confidence: 99%